Inconsistency Norm Peraturan Perkawinan Beda Agama (Studi Undang-Undang No. 1 Tahun 1974 Tentang Perkawinan Dan Undang-Undang No. 23 Tahun 2006 Tentang Administrasi Kependudukan): Inconsistency Norm In Interfaith Regulation (Study On Law No. 1 Of 1974 Concerning Marriage and Law No. 23 Of 2006 Concerning Population Administration) - Dwi Ratna Cinthya Dewi (ISTIDLAL, 2022)
The rules of marriage of different religions that have not been clearly and clearly defined in Law no. 1 Of 1974 concerning marriage. But article 35 letter a in Law no. 23 of 2006 concerning Population Administration provides an opportunity for marriage of different religions. Inkonsistensi this resulted in a conflict of norms. Therefore Lawrence M. Freidman's view is used as an analysis of the legal system in Indonesia. Research conducted to analyze inconsistencies between Law no. 1 of 1974 concerning Marriage with Law no. 23 of 2006 concerning Population Administration and Implications of inconsistencies concerning the regulation of marriage of different religions from legal system theory perspective Lawrence M. Freidman. This research is normative law, using the legislation approach and conceptual approach. Consist of primary law: Law no. 1 Of 1974 Concerning Marriage, Law no. 23 of 2006 Concerning Population Administration, legal system theory Lawrence M. Freidman. Legal material is obtained through documentation method. Then the legal material is analyzed by using qualitative descriptive analysis with related legal system as the theory. Result of research 1. The inconsistence of law due to the mismatch of legislation and the unregulation of marriage regulations of different religions clearly lead to legal uncertainty 2. The implication of inconsistency of marriage rules of different religions according to Lawrence M. Freidman's theory, has not yet achieved the good legal system in Indonesia.